Population implications of lipid lowering for prevention of coronary heart disease: data from the 1995 Scottish health survey. Issue 3 (1st September 2001) - Haq, I U; Ramsay, L E; Wallis, E J; Isles, C G; Ritchie, L D; Jackson, P R
Abstract : OBJECTIVE: To determine the proportion of the population, firstly, with cholesterol ⩾ 5.0 mmol/l and, secondly, with any cholesterol concentration, who might benefit from statin treatment for the following: secondary prevention of coronary heart disease (CHD); primary prevention at CHD risk 30%, 20%, 15%, and 6% over 10 years; and primary prevention at projected CHD risk 20% over 10 years (CHD risk at age 60 years if actual age < 60 years). SUBJECTS: Random stratified sample of 3963 subjects aged 35–64 years from the Scottish health survey 1995. RESULTS: For secondary prevention 7.8% (95% confidence interval (CI) 6.9% to 8.6%) of the population with cholesterol ⩾ 5.0 mmol/l would benefit from statins. For primary prevention, the prevalence of people at CHD risk 30%, 20%, 15%, and 6% over 10 years is 1.5% (95% CI 1.2% to 1.9%), 5.4% (95% CI 4.7% to 6.1%), 9.7% (95% CI 8.8% to 10.6%), and 32.9% (95% CI 31.5% to 34.4%), respectively. At projected CHD risk 20% over 10 years, 12.4% (95% CI 11.4% to 13.5%) would be treated with statins. Removing the 5.0 mmol/l cholesterol threshold makes little difference to population prevalence at high CHD risk. CONCLUSIONS: Statin treatment would be required for 7.8% of the population for secondary prevention. For primary prevention, among other factors, guidelines should take into account the number of patients needing treatment at different levels of CHD risk when choosing the CHD risk to target. The analysis supports a policy of targeting treatment at CHD risk 30% over 10 years as a minimum, as recommended in current British guidelines, with a move to treating at CHD risk 15% over 10 years as resources permit.